A Systemic Approach to School Development Technical Report on the Project School-In - Dalehefte, Inger Marie; Midtsundstad, Jorunn H. (Waxmann Verlag, 2022)
The project School-In was an in-service professional development project which aimed to improve inclusion and facilitate schools' academic results by taking the local context, expectation structures, and school culture into consideration. This intervention project was based on a systemic approach and designed to include the entire teaching staff, ensuring cross-disciplinary and cross-level impact. Conducted in five Norwegian municipalities, School-In was financed by the Research Council of Norway (NFR) as an innovation project for the public sector. This book gives a detailed overview of the project School-In, documenting its research and intervention methods. It provides stakeholders, educational researchers, and practitioners with information about the make-up of the study. In this book, School-In is presented as an example of how new ideas and knowledge can be gained from several research approaches and readers are given specific examples of how development processes may be conducted and investigated in schools.